Evaluation of Antibiotic Sensitivity of the Aural Swab and the Aetiological Factors of Chronic Otitis Media-active Mucosal Type - Saeed Khan, Arshad Abbas, Khalil Ullah, Ali Khan, Muhammad Nadeem, Ayesha Shafi (Pakistan Journal of Medical & Health Sciences, 2023)
The inflammation of the muco-periosteal lining of the middle ear cleft causes the disease known as chronic otitis media (COM). It is characterized by deafness and ear discharge. The children are more prone to this infectious disease. It is the main reason behind hearing impairment. It is creating a challenging scenario for the health care physicians and doctors. Objective: The purpose of this research work was to evaluate the antibiotic sensitivity of the aural swab. The aetiological factors associated with the infection were also studied. Study design: It is a cross-sectional study with the statistical approach. Methods: The study was conducted on 55 patients who attended the ENT and head neck surgery department of Hayatabad Medical Complex Peshawar and M. Islam Medical & Dental College, Gujranwala during the period from January 2021 to June 2022. Out of the 55 patients the 7 patients were diagnosed with bilateral COM. The aural swab was taken from each patient. Each patient was asked to fill the questionnaire for evaluation of the socioeconomic status of the patients. The laboratory and socioeconomic findings were recorded and analyzed by using percentage and frequency. Results: The age group of 31 to 40 years contributed to 24% patients. The 34 patients were male and 21 were female. The percentage ratio was 1:6:1. Out of the 55 patients, 7 were diagnosed with the bilateral COM. The pseudomonas aeruginosa was observed in the 43% cases while S.aureus was observed in the 32% cases. Out of the 33 cases the 81% showed sensitivity to Amikacin, while 75% cases showed sensitivity to Gentamycine and 69% to Ciprofloxacin. Out of the 21 cases of gram positive organisms, 80% showed sensitivity to Amoxyclav, 71% to ceftriaxone and other 71% to Flucoloxacilllin. The sensitivity of the 4 resistant cases against the Meropenem was observed to be 100%. Conclusion: Chronic otitis media is the most common disorder of childhood. A better understanding of the risk factors and antibiotic sensitivity is necessary for the management of treatment strategies. This study provides in-depth knowledge of antibiotic sensitivity and the aetiological factors of the COM. Keywords: Bilateral COM, Aetiological factors, Antibiotic sensitivity, Aural discharge, Pseudomonas aeruginosa